A crítica de MacIntyre à modernidade: liberalismo, individualismo e teorias da justiça - Ruzza, Antonio (2018)
The present thesis aims to discuss A. MacIntyre’s thinking, particularly his moral philosophy and his theory of justice, which rescues the ethics of the virtues of Aristotelian-Thomist inspiration in order to overcome the moral chaos which, according to him, dominates the modern society. He imputes this chaos to Enlightenment´s thinking, which has destroyed a consolidated moral tradition, declaring the independence and autonomy of the individual freed from any authority. The Enlightenment and its heirs (Kant, Hume, and British encyclopedists as their main targets), eliminates the idea of a telos in a human action, as well as relationship between fact and value, and introduces an ethics based on first abstract principles, which are unaware from historical traditions and narratives that is recognized by human groups. The individual has become the great artifact of modernity and individualism it´s dominant ideology. Liberalism is the political-social organization that allows the existence of many modern ethics and these ones are product of French and Industrial Revolutions, which has achieved success thanks to its efficiency and practical results. However, the Liberalism has created an apparently neutral system of laws and rules that regulates conflicts between individuals and classes: any ethical referential has been lost and many moral theories has been emerged in opposition to each other, happened because each one of them reflected different interests and conceptions (among which highlighted the emotivism). MacIntyre presents himself as a great critic of Modernity and its products: Liberalism and Individualism. Concentrating our interest on the problem of inequalities, we show that the Macintyrian proposal for a return to the ethics of virtues (especially those of "recognized dependence" and "fair generosity") and the criterion of merit, applies only to small communities, which by nature are more coercive and controlling, but it doesn’t solve the problem of inequalities in complex societies. We concentrate our efforts in following the evolution of justice concepts since the Middle Age until Rawls and Nozick, which reflects the new vision of the human being as an autonomous individual and as a subject of rights. We conclude that MacIntyre's critique reveals itself as a theoretical analysis of moral disorder in modernity, but not as a political project of transformation, especially since he admits that the attempt to re-establish a community-based society would be "ineffective or disastrous”